2020
DOI: 10.1002/adem.201901570
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of the As‐Cast AlLiCuMgZr Alloy with High Li Content and Different Cu/Mg Ratios

Abstract: Al─Li─Cu─Mg─Zr alloys were prepared from commercially pure Al, Li, Mg, and master alloys of Al-50%Cu and Al-30%Zr. The charges were loaded into a graphite crucible and were heated in an electric resistance furnace under the protection of LiCl-LiF flux and argon gas. They were heated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Peng, et al [5] reported that alloying with Zr could make the grains of Al-Li alloys become isometric, and primary and secondary dendrite arm space of Al-Li alloys could be reduced. Yu, et al [6] also reported that precipitates in as-cast Al-Li-Mg-Cu-Zr alloy were different for different ratio of Cu and Mg. When the ratio of Cu:Mg was higher than 6: 1, the alloy was mainly composed of α(Al), T2(Al 6 CuLi 3 ) and coarse Al 4 Cu 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Peng, et al [5] reported that alloying with Zr could make the grains of Al-Li alloys become isometric, and primary and secondary dendrite arm space of Al-Li alloys could be reduced. Yu, et al [6] also reported that precipitates in as-cast Al-Li-Mg-Cu-Zr alloy were different for different ratio of Cu and Mg. When the ratio of Cu:Mg was higher than 6: 1, the alloy was mainly composed of α(Al), T2(Al 6 CuLi 3 ) and coarse Al 4 Cu 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Although the Al 20 Cu 2 Mn 3 phase can improve the alloy strength, it cannot solve the problem of grain coarsening [ 12 ]. Previous works have evidenced that Al 3 Zr dispersoids formed in 7xxx series alloys via minor Zr addition can significantly improve the inhibition of recrystallization or grain growth, as well as the strength of the alloy [ 13 , 14 , 15 , 16 , 17 ]. Additionally, the two-stage heterogenization treatment produces finer and denser Al 3 Zr dispersoids which help to increase the recrystallization resistance in 7xxx series alloys [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%